2021
DOI: 10.12998/wjcc.v9.i14.3287
|View full text |Cite
|
Sign up to set email alerts
|

Positive psychological intervention for anxiety, depression and coping in subjects addicted to online games

Abstract: BACKGROUND Addiction to online games is not uncommon. The patients usually refuse to take medications and present with affective symptoms such as anxiety, depression and negative coping styles. Psychological intervention based on positive psychology is a promising treatment for such patients. AIM To evaluate the effect of positive psychological intervention on anxiety, depression and coping in people addicted to online games. METHODS This sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…In studies on the effectiveness of positive psychology interventions in different populations with mild and moderate depressive symptoms, it was reported that interventions significantly reduced depression (Bolier et al, 2013b ; Hernandez et al, 2018 ; Taghvaienia & Zonobitabar, 2020 ; Gao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In studies on the effectiveness of positive psychology interventions in different populations with mild and moderate depressive symptoms, it was reported that interventions significantly reduced depression (Bolier et al, 2013b ; Hernandez et al, 2018 ; Taghvaienia & Zonobitabar, 2020 ; Gao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature also suggests that young people with gaming addiction are prone to affective symptoms such as anxiety, depression, and negative coping styles. 62 Moreover, functional neuroimaging studies suggest that gaming addiction might lead to over-connectivity of the default mode and executive control networks that may lead to psychiatric comorbidity. 63 Besides affective disorders, gaming addiction was also found to be associated with attention-deficit hyperactivity disorders (ADHD).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, gaming addiction/gaming disorder is difficult to treat, as medications might be ineffective in managing the addictions. Patients often refuse to take their medication 62 or have poor compliance with behavioural interventions. With the increasing use of digital technologies for gaming, it is essential to teach children and adolescents digital competence to reduce the risk of gaming addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Each exercise mentioned above was practiced in 2 groups daily, with each group practicing 10 times. After each group completes the training, they rested for 1 minute, and the intervention period was 4 weeks; (IV) Psychological counselor: Psychological counselors can use the Hamilton Anxiety Scale (HAMA) (11) to assess the patient's current anxiety state. For patients with anxiety, language can be used to guide them to express their anxiety, understand their physiological and psychological needs, encourage them to express their inner thoughts, and guide patients in relaxation training; (V) Nutrition support: The dietitian can evaluate the current nutritional status of the patient according to the NRS2002 Nutrition Risk Screening Scale (12), which includes three parts: recent weight change, food intake, and disease severity.…”
Section: Neurotrophin Levels Comparisonmentioning
confidence: 99%